PENGARUH BRAND TRUST PADA PERCEIVED VALUE DAN PERCEIVED RISK DAMPAKNYA TERHADAP PURCHASE INTENTION PADA JASA EKSPEDISI JNE DI MARKETPLACE SHOPEE - Sya'diyah, Lailatul; Handriana, Tanti (Jurnal Ilmiah Ekonomi Bisnis, 2024)
One of the key successes of online transactions lies in the final outcome of a product delivery transaction. In this context, the shipping and delivery services plays the pivotal role in the success of such transaction. This research will discuss how an expedition service, JNE is able to create Brand trust so that its existence is recognized by consumers and can generate sustainable purchase intention. The objective of this study is to a positive relationship between Brand trust on perceived value and perceived risk, also the relationship perceived value and perceived risk on purchase intention. The research method employed is quantitative, involving an online survey of 100 respondents. Data analysis in this study utilizes Structural Equation Modeling - Partial Least Square (SEM-PLS) using PLS Version 4 software. The results of this research indicate that Brand trust has a positive influence on perceived value and perceidev risk, perceived value has a positive influence on purchase intention. But, perceived risk has no correlation on purchase intention. The benefits of this research contribute to the study of consumer behavior, particularly regarding brand trust in a courier service, which can positively influence perceived value and negatively affect perceived risk. Additionally, it explores its impact on purchase intention.